Family-based digital literacy management among Muhammadiyah community members in Mataram, Indonesia - Suhadah, Suhadah; Fathurrijal, Fathurrijal; Salwa, Salwa; Setiawati, Geta (Faculty of Communication Sciences Universitas Padjadjaran, 2025)
The rapid development of communication technology in the digital era necessitates significant efforts to address its impacts, beginning with the fundamental unit of society: the family. This research examined digital literacy practices within families of the Muhammadiyah community members in Mataram, West Nusa Tenggara Province, Indonesia. This study, employing a qualitative case study approach, it involved 26 purposively selected informants from Muhammadiyah’s administrators. This study conducted from March to July 2024 and utilized four data collection methods: namely observations, in-depth interviews, questionnaires, and documentation, followed by qualitative analysis. The study revealed that the community generally followed three stages of family-based digital literacy management: First, digital literacy planning and preparation, characterized by internal family agreements and regulations on smartphone use; Second, digital literacy implementation, involving assistance, guidance, and advice on the healthy and correct use of smartphones and social media; and third is evaluation, encompassing control, assessment, and penalties for violations. The Muhammadiyah family-based digital literacy is predominantly preventive and focusing on mitigating negative impacts rather than promoting the positive aspects of technology. This study highlights the importance of comprehensive digital literacy including content and implementation, which should be fostered not only at the personal and family level but also institusionally by community organizations.